2000
DOI: 10.1007/s002400050004
|View full text |Cite
|
Sign up to set email alerts
|

Seminal arginase activity in infertility

Abstract: Arginase (Arg) activity in seminal plasma and sperm cells from infertile men and healthy fertile donors was measured. There were no statistically meaningful differences in seminal plasma Arg activity between the two groups whereas sperm cells from oligospermic infertile men had a higher Arg activity compared with the controls. Some important correlations were established between sperm count and Arg activity (negative values) and sperm motility and Arg activity (positive values) in both sperm cells and plasma s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
1
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 13 publications
2
23
1
2
Order By: Relevance
“…Elgun et al (32) have shown that sperm cells from infertile men with oligospermia have a significantly higher arginase activity than controls. They reported a positive correlation between sperm motility and arginase activity in the infertile group in both seminal plasma and sperm cells.…”
Section: Discussionmentioning
confidence: 99%
“…Elgun et al (32) have shown that sperm cells from infertile men with oligospermia have a significantly higher arginase activity than controls. They reported a positive correlation between sperm motility and arginase activity in the infertile group in both seminal plasma and sperm cells.…”
Section: Discussionmentioning
confidence: 99%
“…Elgun et al. (2000) reported a positive correlation between sperm motility and arginase activity in the infertile group in both seminal plasma and sperm cells.…”
Section: Discussionmentioning
confidence: 95%
“…This value of arginase activity in rams was found higher than that in cat testicular‐specific activity [0.012 U (mg protein) −1 ] (Mahmoud et al. , 2007), normal men [0.016 ± 0.005 U (mg protein) −1 ] and men with oligospermia [0.029 ± 0.009 U (mg protein) −1 ] (Elgun et al. , 2000).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…(13,(24)(25)(26) It is therefore important to establish a convenient and sensitive ELISA method for measuring arginase. We therefore developed an efficient ELISA system for measuring the concentration of human liver-type arginase in both serum and culture medium.…”
Section: Resultsmentioning
confidence: 99%